2022
DOI: 10.3389/fpsyt.2022.847310
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Lipid Signatures in Post-traumatic Stress Disorder

Abstract: BackgroundResearch assessing lipid levels in individuals diagnosed with post-traumatic stress disorder (PTSD) has yielded mixed results. This study aimed to employ meta-analytic techniques to characterize the relationship between the levels of lipid profiles and PTSD.MethodsWe performed meta-analyses of studies comparing profiles and levels of lipids between PTSD patients and healthy individuals by searching Embase, Ovid Medline, Scopus, PsycINFO, and Cochrane databases for the studies until March 2021. Meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Stress-related disorders usually follow a stressful event or psychological trauma . The elevated levels of glucose and TG observed in individuals with such diagnoses could be indicative of a maladaptive autonomic response, including aberrant sympathetic activity that often occurs in individuals previously exposed to a traumatic event . This finding indicates the need for early identification of patients at risk for persistent psychiatric response to trauma or significant life changes, because early intervention can prevent disease progression and cardiometabolic comorbidities …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress-related disorders usually follow a stressful event or psychological trauma . The elevated levels of glucose and TG observed in individuals with such diagnoses could be indicative of a maladaptive autonomic response, including aberrant sympathetic activity that often occurs in individuals previously exposed to a traumatic event . This finding indicates the need for early identification of patients at risk for persistent psychiatric response to trauma or significant life changes, because early intervention can prevent disease progression and cardiometabolic comorbidities …”
Section: Discussionmentioning
confidence: 99%
“…57 The elevated levels of glucose and TG observed in individuals with such diagnoses could be indicative of a maladaptive autonomic response, including aberrant sympathetic activity that often occurs in individuals previously exposed to a traumatic event. 58,59 This finding indicates the need for early identification of patients at risk for persistent psychiatric response to trauma or significant life changes, because early intervention can prevent disease progression and cardiometabolic comorbidities. 60 The absence of a modifying effect of sex on the association of metabolic biomarkers with depression, anxiety, and stress-related disorders is in line with a previous study.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…PTSD is reported to be significantly associated with higher BMI, and particularly with central obesity [ 33 , 34 ]. Multiple studies including meta-analysis showed PTSD patients have higher levels of LDL-C and triglycerides, but lower level of HDL-C compared to healthy controls [ 35 ]. Increased fasting blood glucose (hyperglycemia) and insulin are also observed among PTSD patients [ 12 ], [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Damage to brain neuroplasticity and other mechanisms ultimately affects cognitive, behavioral, and emotional responses ( Sanacora et al, 2022 ). A recent systematic review suggested dysregulation of lipids that may serve as biomarker to predict the risk of PTSD ( Bharti et al, 2022 ).…”
Section: Effects Of Lipids On Post-traumatic Stress Disorder Comorbid...mentioning
confidence: 99%